Fenomena Thrift Shopping Di Kalangan Masyarakat Akibat Perubahan Gaya Hidup Hidup Modern (Studi Globalisasi Di Wilayah Jawa Timur) - Syaraahiyya, Ahyan; Rusadi, Emmy Yuniarti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The impact of the globalization trend is the emergence of foreign cultures that are starting to enter Indonesia which causes a new lifestyle in terms of dressing. Most people want to follow a trending lifestyle but don't want to spend a lot of money. This condition causes the activity of shopping for used goods to be popular in Indonesia. Modernization is growing rapidly because it has many ways to access information from various countries easily and quickly. This study aims to determine the phenomenon of thrift shopping among the community due to changes in modern lifestyles. This research was conducted using a descriptive research method using a quantitative survey approach.